Flexible Mott Synaptic Transistor on Polyimide Substrate for Physical Neural Networks. (15th April 2022) - Wu, Zhenfa; Shi, Peng; Xing, Ruofei; Yu, Tongliang; Zhao, Le; Wei, Lin; Wang, Dong; Yan, Shishen; Tian, Yufeng; Bai, Lihui; Chen, Yanxue
Abstract: Flexible synaptic devices that emulate biological synapses are the key to developing wearable intelligent equipment. However, there are still challenges to achieving multiple synaptic functions in flexible synaptic devices and realizing large‐scale production of synaptic devices. Herein, a flexible synaptic transistor on polyimide substrate is designed and fabricated using a solid‐state electrolyte gate and a VO2 Mott insulator thin film channel. Four orders conductance modulation is obtained in the VO2 thin film channel across the metal‐insulator transition. Several essential synaptic behaviors, including potentiation, depression, and short‐term/long‐term plasticity, are successfully demonstrated in this flexible synaptic device. More importantly, this synaptic transistor exhibits high cycling stability and good tolerance to bending deformation. A simulated artificial neural network built from this synaptic device achieves high recognition accuracy of 98% in the flat state and 92% in the bending state. In addition, this flexible device is fabricated on polyimide substrate by magnetron sputtering method, which has low cost and is compatible with modern semiconductor technology. This work can pave the way for large‐scale production of flexible synaptic Mott transistor devices. Abstract : High quality amorphous VO2 film is grown directly on polyimide substrate without a buffer layer by magnetron sputtering. A flexible all‐solid‐state artificial synaptic transistor is successfully fabricated. The device shows multi‐states storage functions and exhibits excellent stability and high recognition accuracy. Furthermore, the low cost of polyimide and large‐scale production of the sputtering method pave the way for wearable artificial intelligence equipment.